The development of a physical therapy service to treat urinary incontinence: Results of a RE-AIM evaluation - Brosina de Leon, Elisa; Cardoso, Maria Natália; de Brito, Elorides; dos Santos, Maira Mendes; Almeida, Fabio Araujo (Frontiers in Global Women's Health, 2022)
Background: A conservative physiotherapy service development addressed to treat urinary incontinence for older women was studied using the RE-AIM (reach, effectiveness, adoption, implementation, and maintenance) framework. Design: We conducted a pragmatic case study design based on RE-AIM. Settings/participants: Included women ≥ 60 years of age, with self-reported UI symptoms. Results: A total of 34 older women were enrolled in the service with a mean age of 61.53 years. There was a significant improvement in the strength of the pelvic floor muscles, power, endurance, and fast contraction capacity after the intervention, however, it was observed a high dropout rate. Program implementation was supported by Physical Therapy teams who engaged in care coordination. The program has been maintained for over 4 years. Conclusion: Our findings demonstrate that UI patients would benefit from physiotherapy treatment and that this intervention is feasible. This RE-AIM evaluation provides lessons learned and strategies for future adoption, implementation, and maintenance of a Physical Therapy pelvic service.